Bot Permainan Tebak Gambar Pengenalan Adat Istiadat Riau pada Aplikasi Line dengan Metode Webhooks - Prayoga, Asep; Nurjayadi, Nurjayadi (Jurnal Teknologi Terpadu, 2018)
Customary Riau Islands are becoming increasingly forgotten by children and teenagers today, they are only busy with gadgets and social media. With this game, we can get to know Riau customs such as special food, tourist attractions, or dance. The author is interested in making this because the bot that is used is run on the social media line, where social media is very crowded by the public. This bot uses web hosting to make it easy and not slow, using the MySQL database for storing questions and answers, the programming language used is PHP. And the method of webhooks is a method to make a callback from a website to an application in real time. The results of this study are in the form of a Game Bot account that can be used by people by opening a Bot account chat or by adding this Bot account to a chat group.